Nitric Oxide - Its Importance in Swallowing, Inflammatory Bowel Disease and Cirrhotic Cardiomyopathy - ABR Thomson (Canadian Journal of Gastroenterology)
Nitric oxide is a neurotransmitter found in the central and peripheral nervous systems. Nitric oxide synthase (NOS) is localized in the central nervous system, including the nucleus of the solitary tract, nucleus ambiguus and dorsal motor nucleus of the vagus. These are regions that are implicated in the central control of swallowing and esophageal motility. In rats and rabbits, NOS has been shown to be present in the nucleus subcentralis of the nucleus of the solitary tract, and is thought to be responsible for the central programming of the striated muscle component of esophageal peristalsis. Beyak and co-workers from the University of Toronto, Toronto, Ontario provided evidence that the L-arginine-nitric oxide pathway is implicated in the central control of swallowing and esophageal motility. They studied oropharyngeal swallowing as well as esophageal peristalsis, and determined the functional role of brain stem nitric oxide by examining the effects of blockade of central nervous system NOS on swallowing, and on primary and secondary peristalsis. Administering NOS inhibitors intravenously or intracerebroventricularly into the fourth ventricle produced a number of oropharyngeal swallows and induced primary peristalsis in the smooth muscle portion of the esophageal body. NOS reduced the number of oropharyngeal swallows and the incidence of primary peristalsis in both smooth and striated muscle, and reduced the amplitude of peristalsis and smooth muscle contraction. This suggests that nitric oxide is a functional neurotransmitter in the central pattern generator responsible for swallowing and the central control of esophageal peristalsis. Peripherally administered NOS inhibitor can access structures within the blood-brain barrier to affect neuronal activity and physiological function. The central pattern generated for swallowing and esophageal peristalsis is suggested to be a serial network of linked neurons within the nucleus of the solitary tract and neighbouring reticular formation, and there is likely one subnetwork for the oropharyngeal phase and the other for the esophageal phase of swallowing. The neurosubstances mediating striated and smooth muscle peristalsis may be both anatomically and neurochemically distinct. The role of nitric oxide in the pathogenesis of esophageal motility disorders remains to be established.